Development of Instagram-Based Digital Chemistry Teaching Materials Integrated with Batak Toba Ethnopedagogy for Acid–Base Learning - Rabiah Afifah Daulay; Marnida Yusfiani; Purnama Sari; Dinda Dwi Hasanah; Muhammad Ali Athiya Zahran; Amelia Rahmadhani; Ari Ramadana; Olivia Febriana Gea (LPPM Universitas Negeri Jakarta, 2026)
Scientific literacy remains one of the major challenges in chemistry education in Indonesia, particularly in acid–base learning, which involves abstract concepts and complex representations. At the same time, the widespread use of social media among students provides opportunities to develop innovative digital learning resources that are contextual and engaging. This study aimed to develop Instagram-based chemistry digital teaching materials integrated with Batak Toba ethnopedagogy for acid–base learning and to evaluate their validity and practicality. The study employed a Research and Development (R&D) approach using the ADDIE model, limited to the Analysis, Design, and Development stages. The needs analysis involved three chemistry teachers and 30 senior high school students. The developed product was validated by three expert validators and tested through a limited practicality trial involving 17 Grade XI students from MAN 1 Medan. Data were collected using interview guidelines, needs analysis questionnaires, validation sheets, and practicality questionnaires and were analyzed using percentage techniques. The results showed that the developed teaching materials achieved a material validity score of 92.00% and a media validity score of 91.85%, both categorized as very valid. The limited practicality trial resulted in an average practicality score of 76.32%, categorized as practical. These findings indicate that the developed teaching materials are valid and practical for supporting acid–base learning. The integration of Batak Toba ethnopedagogy through the Mangongkal Holi tradition provides a contextual learning environment that connects chemistry concepts with students’ cultural experiences. Therefore, the developed teaching materials have the potential to support culturally responsive chemistry learning and strengthen students’ scientific literacy.